Urban Farming as a Solution for Food Independence and New Job Opportunities in Bangka Belitung: A Case Study of Pangkalpinang City (International Journal of Economics and Management Research, 2026)
This study, titled “Urban Farming as a Solution for Food Self-Sufficiency and New Employment Opportunities in Bangka Belitung: A Case Study of Pangkalpinang City,” investigates the implementation of urban farming as an adaptive strategy to address food insecurity and unemployment in urban areas with limited agricultural land. Pangkalpinang City faces increasing challenges related to urbanization, including declining agricultural land, high dependence on external food supplies, and limited job opportunities for residents. The purpose of this research is to analyze how urban farming contributes to food self-sufficiency, the creation of new employment opportunities, and community participation in sustainable urban agriculture. Using a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and documentation studies, and analyzed thematically and through SWOT analysis to identify internal and external factors influencing urban farming development. The findings reveal that urban farming in Parit Lalang, Pangkalpinang, is predominantly conducted on small home gardens and vacant lots using hydroponic and traditional methods, with participants mainly consisting of productive-age residents and housewives. The practice has enhanced household food availability, reduced living costs, and generated additional income, thereby improving local economic resilience. However, several challenges persist, such as limited technical skills, financial constraints, and inconsistent government support. The study concludes that strengthening training programs, improving financial access, and developing pilot projects in each subdistrict are essential to optimize the sustainability of urban farming as a strategy for food security and community empowerment in urban settings